PENGKLASIFIKASIAN KETAHANAN JENIS BAMBU 20 TERHADAP RAYAP KAYU KERING - Jasni; Ratih Damayanti; I.M. Sulastiningsih (Jurnal Penelitian Hasil Hutan, 2017)
The resistance of twenty bamboo species from different regions of Indonesia were tested against drywood termites (Cryptotermes cynocephalus Light.). Each bamboo species was cut into dimension of 5 cm × 2.5 cm × 1 cm. The test was conducted according to SNI 7207-2014. Parameters mass loss percentage of bamboo, survival rate of the termites, and degree of attack (subjectively) were observed as the basic to classify the resistance of bamboo against drywood termites. According to the mass loss percentage, the bamboo species were assigned into five groups: two bamboo species as resistance class I, six bamboo species as class II, five bamboo species as class III, four bamboo species as class IV, and three bamboo species as class V. Based on the survival rate of the termites, the natural resistance of bamboo could be assigned into five groups: two bamboo species as resistance class I, one species as class II, ten bamboo species as class III, five bamboo species as class IV, and two bamboo species as class V. The classification according to the degree of attack showed that two bamboo species experienced severely attack (38 - 40.5% / score 90), while the rest eighteen bamboo species had medium attack (18.4 - 34.9% / score 70).